MATHEMATICAL MODELING AS A POWERFUL TOOL FOR PROVIDING QUALITY OF HIGHER EDUCATION (Innovative Technologica: Methodical Research Journal, 2023)
This article presents the importance, necessity and essence of the use of mathematical models, which are considered a powerful tool in higher education in the specialty of biology and medicine, as a powerful tool in the research work of scientific researchers, as well as to study the features of using the methodology of mathematical modeling in the study of the activity of biological systems. As an example of mathematical modeling, an example is given of the construction of a mathematical model that represents the regulatory mechanisms of cardiac activity.